Microeconomic theory : - Nicholson, Walter (Dryden Press, 1998)
The book provides a comprehensive approach to modern microeconomics. This is accomplished by providing intuititive explanations of the principal results and by stressing the common mathematical structures of many economic problems, including a consistent framework for examining optimizing behavior under conditions of risk aversion, welfare calculations maded in a variety of applications, discussion of price discrimination